Effects of ring machine apron and cot components on yarn quality - (:unkn) unknown (My University, 2013)
Aprons and cots that are used in the drafting system have important influences on yarn quality. In this study, 176 mtex and 26.6 mm of fiber length of cotton roving of 909 tex were blended with various cottons ( 42 % Turkey, 40 % Uzbekistan, 16 % Tajikistan and 2 % Ethiopian). The 20 tex (atex, 37.4) cotton yarns were produced at spindle speed of 15093 rev/min with 42 mm ring diameter and a 45 mg C type traveller (No. 3/0) in ring frames. The effects of cots and aprons on quality of yarns (breaking tenacity, elongation, irregularity and hairiness) were examined under all conditions. In each experiment four yarns were produced and the results of the experiments were given as their average. The yarn and twist values were fixed; the effects of variation of only apron and cots on yarn quality were studied. The experiments were analyzed in order to determine which parameters had significant effects on yarn properties. This experiment showed that cot and apron quality has direct influence on the yarn quality.
Keywords: Apron; Cot; Cotton yarn; Grinding machine; Ring machine